Spatiotemporal distribution of ichthyoplankton and their relationship with environmental factors in the waters around the Yellow River estuary, China - Niu, Mingxiang; Lu, Feng; Zuo, Tao; Wang, Jun; Li, Yongtao; Cheng, Zhaolong; Sun, Jianqiang (Frontiers in Marine Science, 2025)
IntroductionThe Yellow River estuary serves as a crucial convergence point between the Yellow River and the Bohai Sea and is a vital spawning, nursery, and feeding ground for a variety of fish species. Ichthyoplankton are essential for the replenishment and sustainable use of fishery resources. To gain insights into the distribution of fish in these early life stages and examine in depth the impacts of environmental factors on their presence and abundance in the waters around the Yellow River estuary, in this study, we analyzed the temporal and spatial distribution of ichthyoplankton and their correlation with environmental variables.MethodsData were gathered from horizontal-trawl surveys conducted between April and July of 2020, 2021, and 2023. In instances where no eggs or larvae were caught, a two-stage Generalized Additive Model (GAM) was employed to evaluate the influence of environmental factors on the presence/absence (P/A model) and abundance, given presence (Density model).ResultsThe results revealed that there were significant fluctuations in species richness both monthly and annually. Moreover, notable spatial disparities were identified in the distribution of abundance encompassing estuarine, settled, and migratory fish populations. The final model accounted for 38.69% and 39.80% of the deviance in the presence and abundance of ichthyoplankton, respectively. The two-stage GAM results highlighted that sea surface temperature (SST), chlorophyll a concentration, sea bottom salinity, and water depth were the dominant factors influencing the presence of ichthyoplankton. Moreover, a model incorporating SST, sea surface salinity, and distance to shore best described the abundance of ichthyoplankton when present.DiscussionOur findings contribute to understand the spatiotemporal dynamics of ichthyoplankton and their influencing factors in the waters around the Yellow River estuary, which have important implications for fisheries management.